Reflejos y huellas de la arquitectura del movimiento moderno en el noticiario documental español no-do - Dda. Noemí RUBIO POZUELO (Fonseca, Journal of Communication, 2023)
This paper is based on the relationship established between cinematography and architecture, which is considered a fundamental connection insofar as it is constituted as a paradigm of compositional and aesthetic fecundity. Starting from this correspondence, we propose an approach to the representation of architecture from a filmic perspective. In particular, we refer to the Spanish architectural production developed during the Franco regime, which could have been influenced by the Modern Movement and could havebeen collected in the NO-DO Documentary Newsreel.